2018
DOI: 10.1002/slct.201800172
|View full text |Cite
|
Sign up to set email alerts
|

Studies on DNA Interaction with 2(3),9(10), 16(17), 23(24)‐Tetrakis 2((4‐Phenoxyphenyl) Diazeylbenzoic acid)phthalocyaninato Zinc (II) Compound

Abstract: In this study, 2(3), 9(10), 16(17), 23(24)‐tetrakis 2((4‐phenoxyphenyl) diazeylbenzoic acid)phthalocyaninato zinc (II) compound was chosen to study DNA binding activities. The binding activities of zinc (II) phthalocyanine compound bearing 2(3),9(10), 16(17), 23(24)‐tetrakis 2((4‐Phenoxyphenyl) diazeylbenzoic acid) ligand with Calf Thymus (CT)‐DNA was investigated using absorption titration, fluorescence spectroscopy, cyclic voltammetry and thermal melting profile in a Tris‐HCl buffer system at pH 7.0. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…It is observed that ΔT m value of 4–6 °C for complexes 1 and 2 was much larger than ΔT m < 2 °C for electrostatic DNA binder [Ru(bpy) 3 ] 2+ , but lower than that of traditional intercalator ethidium bromide (EB) with ΔT m of 13 °C . These results suggested groove binding interaction along with partial intercalative behavior of complexes 1 and 2 inside the DNA helix in conformity with electronic absorption spectra and viscosity studies …”
Section: Dna Binding Studiesmentioning
confidence: 54%
“…It is observed that ΔT m value of 4–6 °C for complexes 1 and 2 was much larger than ΔT m < 2 °C for electrostatic DNA binder [Ru(bpy) 3 ] 2+ , but lower than that of traditional intercalator ethidium bromide (EB) with ΔT m of 13 °C . These results suggested groove binding interaction along with partial intercalative behavior of complexes 1 and 2 inside the DNA helix in conformity with electronic absorption spectra and viscosity studies …”
Section: Dna Binding Studiesmentioning
confidence: 54%
“…The gel electrophoresis experiments were recorded at 80 V during 3 h in the buffer solution (TBE) and the bands of the DNA were photographed using a BioRad system. In this method, the measurements were carried out with a Thermo Scientific gel electrophoresis system [29][30][31][32].…”
Section: Dna Binding Studiesmentioning
confidence: 99%